Feature : Meet the ultras. (3rd September 2018) - Skuse, Benjamin
Abstract: Ultrahigh-energy cosmic rays are the most energetic and rarest of particles in the universe – and also one of the most enigmatic. Benjamin Skuse reveals how cosmic-ray mysteries are continuing to test our understanding of high-energy physics